Induced automation: Evidence from firm-level patent data - Antoine Dechezleprêtre; David Hémous; Morten Olsen; Carlo Zanella (University of Zurich, Department of Economics, 2021)
Do higher wages lead to more automation innovation? To answer this question, we first use the frequency of certain keywords in patent text to create a new measure of automation innovation in machinery. We show that our measure is correlated with a reduction in routine tasks in a cross-sectoral analysis in the US. We combine macroeconomic data from 41 countries and information on geographical patent history to build firm-specific measures of low- and high-skill wages. In a firm-level panel analysis, we find that an increase in low-skill wages leads to more automation innovation with an elasticity between 2 and 5. Placebo regressions show that the effect is specific to automation innovations. Finally, we focus on a specific labor market shock, the German Hartz reforms, and show that they reduced automation innovations by those non-German firms relatively more exposed to Germany.
Keywords: O31; O33; J20; 330; Automation; innovation; patents; income inequality